2023
DOI: 10.1101/2023.10.09.561542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pial collaterals develop through mosaic colonization of capillaries by arterial and microvascular endothelial cells

Tijana Perovic,
Irene Hollfinger,
Stefanie Mayer
et al.

Abstract: Collaterals are unique blood vessels present in many healthy tissues that cross-connect distal-end arterioles of adjacent arterial trees, thus providing alternate routes of perfusion. Stroke patients with superior pial collateral flow respond better to treatments and present with an overall improved prognostic outcome. However, how pial collaterals develop in the embryo and how they reactivate upon stroke remains unclear. Here, using lineage tracing in combination with three-dimensional imaging, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…We demonstrate the formation of collateral arteries from pre-existing arterial lineage as observed 9,10,13,22 or proposed 6 earlier. While this manuscript was in progress, Perovic et al reported that two separate vascular lineages populate pial collaterals.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…We demonstrate the formation of collateral arteries from pre-existing arterial lineage as observed 9,10,13,22 or proposed 6 earlier. While this manuscript was in progress, Perovic et al reported that two separate vascular lineages populate pial collaterals.…”
Section: Discussionsupporting
confidence: 80%
“…While this manuscript was in progress, Perovic et al reported that two separate vascular lineages populate pial collaterals. 10 We also observed that well-formed pial collaterals are majorly populated by artery cells, and minimally by capillaries. Intra-vital imaging of embryonic brains reveal that pre-existing artery cells extend along defined microvascular paths to connect and build pial collaterals.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations